Analisis Korelasi Umur, Massa Tubuh dan Faktor Eksposi Terhadap Entrance Surface Air Kerma pada Pemeriksaan Thorax di Rumah Sakit Universitas Andalas - Sari, Suci Indah; Milvita, Dian; Fardela, Ramacos; Pratama, Ida Bagus Gede Putra; S, Amel Oktavia (Universitas Andalas, 2024)
Research has been conducted on the correlation analysis of age, body mass, and exposure factors to Entrance Surface Air Kerma (ESAK) in the Radiology Installation of Andalas University Hospital. The study was conducted by collecting data on adult thorax examination patients over 15 years of age and body mass (60 ± 10) kg in Posterior-Anterior (PA) and Anterior-Posterior (AP) projections for ± 5 months. Patient data used in PA projections are 107 patient data with the Automatic Exposure Control (AEC) method, 9 patient data with manual methods and 10 AP projection patient data with manual methods. Analysis was conducted using the Pearson correlation test. The results showed that body mass and exposure factors have a very strong relationship with ESAK as indicated by r = 0.805 to 0.990. As body mass and exposure factor increase, the average ESAK received by patients will increase, while age has a weak relationship with ESAK as shown by r = -0,246 to 0,227.